Fun fearless females to the fore a content analysis of articles on contraception in Cosmopolitan magazine Philippines - Pio, Ana Cassandra T.
One of the talked about issues in the country today is the implementation of the Reproductive Health Bill, the rise of HIV cases has put pressures on the different sectors of the country to educate Filipinos on reproductive health. According to some studies however, the media is the primary source of information for most people. Cosmopolitan Magazine has been providing such information all along even before the debate has started. Its slogan ?Fun, fearless feminism? empowers women to take control of their sexuality. The study was conducted to find out if the information provided in the magazine not only encourages women to be sexually-empowered but to be aware of contraception and its methods and tools as well. The researcher analyzed the content of articles in 12 editions Cosmopolitan Magazine Philippines 2008 pertaining to reproductive health and habit including advertisements. Information such as length and position were also recorded. The data gathered were interpreted using the first and second level of agenda-setting theory. They answer the questions what to think and how to think, respectively. This determined not only the frequency and placement, but also the message of the articles. The study encompassed 114 articles, the majority of which are in the form of advertisements. The condom is mentioned in 35 out of 54 articles. A bulk of the articles discussed the issue of prevention, cause/s and treatments of sexually-transmitted diseases and reproductive tract infections. Although the study showed the articles on contraception are not highlighted and are found mostly in the later pages of the magazine, it has been shown that sexual health is indeed very important for the fun, fearless Filipinia.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts